Evaluating Adaptive Droop Control for Steady-State Power Balancing in DC Microgrids Using Controller Hardware-in-the-Loop - Beatriz C. Moura; Pedro José dos Santos Neto; Danillo B. Rodrigues; Érico Chagas Guimarães; Luiz Carlos G. Freitas; João Pedro Carvalho Silveira; Gustavo Brito de Lima (Eletrônica de Potência)
DC microgrids (DCMGs) have been gaining attention due to their advantages over AC microgrids. The most commonly used control technique for DCMGs is droop control. Despite its benefits, droop control has drawbacks, such as power mismatch and deviations in DC bus voltage, often caused by differences in line resistance among grid-forming power electronics converters. To address these issues, the article proposes an adaptive droop control technique to correct steady-state power imbalances between grid-forming units in the DCMG. Additionally, a hierarchical voltage level is introduced to regulate the DC bus voltage. The analyzed DCMG includes two energy storage units, electronic loads, and a renewable energy source, each with its respective power electronic converter. The proposed technique uses real-time output power measurements from the energy storage system to calculate line resistance differences, incorporating these into the adaptive droop calculation. Several operating conditions are tested using a controller hardware-in-the-loop. The results validate the proposed technique and design guidelines.